2018
DOI: 10.3390/ijms19020608
|View full text |Cite
|
Sign up to set email alerts
|

Presence of TERT Promoter Mutations is a Secondary Event and Associates with Elongated Telomere Length in Myxoid Liposarcomas

Abstract: The occurrence of TERT promoter mutations has been well described in soft tissue sarcomas (STS). However, the biological role of these mutations as well as their impact on telomere length in STS is still unclear. We analyzed 116 patient samples diagnosed with 22 distinct histological subtypes of bone and STS for the occurrence of TERT promoter mutations by Sanger sequencing. We observed TERT promoter mutations at an overall frequency of 9.5% distributed over 7 different sarcoma subtypes. Except for one chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 73 publications
1
9
2
Order By: Relevance
“…It exhibits the reciprocal translocation, t(12;16)(q13;p11), in approximately 95% of patients, which results in the fusion of FUS‐DDIT3, and t(12;22)(q13;q12) in nearly 5% of patients, resulting in the formation of EWSR1‐DDIT3 20,21 . Soft tissue sarcomas generally show a high frequency of ALT, while MLPS is the only exception and is known to have a high prevalence of TERT promoter ( TERT p) mutations (22.2%‐79.1%) 5,14,22‐26 . It has also been reported that 5%‐18% of patients with MLPS have ALT, 27,28 and telomerase activation and ALT are not mutually exclusive 27 .…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits the reciprocal translocation, t(12;16)(q13;p11), in approximately 95% of patients, which results in the fusion of FUS‐DDIT3, and t(12;22)(q13;q12) in nearly 5% of patients, resulting in the formation of EWSR1‐DDIT3 20,21 . Soft tissue sarcomas generally show a high frequency of ALT, while MLPS is the only exception and is known to have a high prevalence of TERT promoter ( TERT p) mutations (22.2%‐79.1%) 5,14,22‐26 . It has also been reported that 5%‐18% of patients with MLPS have ALT, 27,28 and telomerase activation and ALT are not mutually exclusive 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The increased expression of telomerase is predominantly caused by mutations of the TERT promoter 38 (Figure 4A) and, less frequently, by gene amplification or rearrangements 34,39 . Several studies have identified TERT promoter SNV mutations in different sarcomas 40–45 . TERT promoter mutations have been commonly identified in multiple subtypes, including atypical fibrous xanthoma (25 of 27 cases, 93%), pleomorphic dermal sarcoma (26 of 34 cases, 76%), myxoid liposarcoma (57 of 94 cases, 61%), and solitary fibrous tumour (38 of 176 cases, 22%).…”
Section: Hallmark 5: Enabling Replicative Senescencementioning
confidence: 99%
“…TERT promoter mutations have been commonly identified in multiple subtypes, including atypical fibrous xanthoma (25 of 27 cases, 93%), pleomorphic dermal sarcoma (26 of 34 cases, 76%), myxoid liposarcoma (57 of 94 cases, 61%), and solitary fibrous tumour (38 of 176 cases, 22%). USTSs, on the other hand, rarely harbour TERT promoter SNV mutations (<2% of cases), 7,41,43,44 but a subset of cases show recurrent complex structural rearrangements of chromosome 5p15.33, which lies proximal to TERT (Figure 4B). 7 These 5p15.33 rearrangements juxtapose the TERT coding sequence to strong enhancer elements that transcriptionally up‐regulate telomerase in a similar manner to that seen in some neuroblastomas 7,46 .…”
Section: Hallmark 5: Enabling Replicative Senescencementioning
confidence: 99%
“…Mutations in the TERT promoter region were identified by PCR and Sanger sequencing as described previously [31]. The detailed protocol can be found in the Supplementary Materials and methods.…”
Section: Dna Extraction Polymerase Chain Reaction and Mutational Anamentioning
confidence: 99%
“…TL analysis was done by a modified protocol of immunoquantitative fluorescence in situ hybridization (Q-FISH) as previously described [31][32][33][34][35]. FFPE sections of the cohort were deparaffinized and rehydrated before antigen retrieval in 10 mM citrate buffer (pH 6.0).…”
Section: Quantitative Fluorescence In Situ Hybridization (Q-fish)mentioning
confidence: 99%